2020
DOI: 10.1002/jcph.1632
|View full text |Cite
|
Sign up to set email alerts
|

Exposure‐Response Analysis of Vamorolone (VBP15) in Boys With Duchenne Muscular Dystrophy

Abstract: Exposure‐response relationships of vamorolone, a novel dissociative steroidal anti‐inflammatory drug, were investigated in clinical trials in boys with Duchenne muscular dystrophy. Variables were clinical outcome measures, Fridericia‐corrected QT (QTcF) duration, and pharmacodynamic (PD) biomarkers. Exposure metrics were area under the plasma concentration time curve (AUC) and maximum plasma concentration (Cmax), with a sigmoid Emax model applied. Significant improvement in clinical efficacy outcomes was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The first multiple ascending dose (MAD) cohort trial tested pharmacokinetics (PK) and safety for 2 weeks of drug dosing followed by a 2-week washout (VBP15-002) [11]. Vamorolone treatment in this study showed no dose-limiting toxicities, and PK demonstrated a short half-life similar to corticosteroids (~2 hours), no drug accumulation, similar PK on day 1 and day 14, and PK similar to that of healthy adult male volunteers (VBP15-001) [9,[11][12][13]. All DMD participants completed the MAD study and then continued on the same dose for a 24-week dosefinding (efficacy and safety) extension study (VBP15-003).…”
Section: Plos Medicinementioning
confidence: 99%
“…The first multiple ascending dose (MAD) cohort trial tested pharmacokinetics (PK) and safety for 2 weeks of drug dosing followed by a 2-week washout (VBP15-002) [11]. Vamorolone treatment in this study showed no dose-limiting toxicities, and PK demonstrated a short half-life similar to corticosteroids (~2 hours), no drug accumulation, similar PK on day 1 and day 14, and PK similar to that of healthy adult male volunteers (VBP15-001) [9,[11][12][13]. All DMD participants completed the MAD study and then continued on the same dose for a 24-week dosefinding (efficacy and safety) extension study (VBP15-003).…”
Section: Plos Medicinementioning
confidence: 99%
“…Vamorolone (previously known as VBP-15) is a novel anti-inflammatory steroid analog that is currently being studied as a replacement for traditional glucocorticoid treatment for DMD. 35 This drug acts in a similar way to other glucocorticoids by binding to the GR but not to GREs. As such, the adverse effects associated with traditional glucocorticoids are expected to be significantly lower with the use of vamorolone.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Further, when delivered orally to B6AJ mice, it decreased lipid mobility, increased muscle repair, and reduced fatty replacement of myofibers, all of which were made more severe by prednisone treatment [186]. Currently, vamorolone is in clinical trials as an antiinflammatory for DMD/BMD, and preliminary findings reported fewer adverse events and some improved motor function [30,187]. While the data are intriguing, there are no trials in LGMD2B or MM patients currently.…”
Section: Dysferlinopathymentioning
confidence: 99%